The Evolution of Islamic Da'wah in the Age of Social Media: The Role of Waqf Institutions - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Yakubu Zulaihat Mohammed; Ibrahim Abubakar Muhammad; Abubakar Sadiq Magaji (CV. Media Inti Teknologi, 2025)
This paper aim to examine how Islamic Da'awah, has changed in the digital era with an emphasis on social media's revolutionary impact and the incorporation of Waqf, institutions to aid in these endeavors. The advent of social media platforms has brought about tremendous changes to Islamic Da'awah, since they have made it easier for Islamic teachings to be widely disseminated and have encouraged global communication and interaction between Muslims and non-Muslims. Islamic scholars, preachers, and individuals have been able to dispel misconceptions about Islam and impart religious information by using easily accessible platforms like Facebook, YouTube, Instagram, and Twitter. This paper uses a qualitative research approach to examine how Islamic da'awah has changed in the era of social media and how Waqf institutions assist. It does this by combining case studies, literature reviews, and content analysis. The findings of the research revealed that digital media has a significant role in forming modern Muslim identity, expanding its benefits to reach national and international community, advancement of da’awah activities and posing certain risks, such as the possibility of radicalization and disinformation. The study concludes that working together with academics, content producers, and Waqf organizations will be essential to making sure that Da'awah in the digital age is based on Islamic teachings and makes the most of contemporary technology.